2016
DOI: 10.3892/ol.2016.4228
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 participates in PLK1-regulated cell cycle progression in renal cell cancer cells

Abstract: Abstract. The regulation of entry into and progression through mitosis is important for cell proliferation. Polo-like kinase 1 (PLK1) is involved in multiple stages of mitosis. Forkhead box protein M1 (FOXM1) has multiple functions in tumorigenesis and, in elevated levels, is frequently associated with cancer progression. The present study reports that FOXM1, a substrate of PLK1, controls the transcription mechanism that mediates the PLK1-dependent regulation of the cell cycle. The present study investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…These results indicate that PLK1 upregulation may be involved in cancer progression and invasion. This is in line with the results of previous studies [60], [61], [62].…”
Section: Plk1 and Human Cancersupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate that PLK1 upregulation may be involved in cancer progression and invasion. This is in line with the results of previous studies [60], [61], [62].…”
Section: Plk1 and Human Cancersupporting
confidence: 93%
“…In addition to the tumor suppressors, PLK1 interacts with other classes of genes or proteins such as kinases: AURKA [84], [85], BUB1 [86], [87], and WEE1 [88]; oncogenes: MDM2 [89] and FOXO3 [90]; and transcriptional factors: HSF1 [91], [92], [93], RELA [94], TRIOBP [95], and FOXM1 [62], [96], [97], [98], etc. These interactions may be essential for PLK1 to play an important role in regulation of the cell cycle, and dysfunction of the interactions could be associated with cancer and other diseases.…”
Section: Plk1 and Human Cancermentioning
confidence: 99%
“…FOX transcription factor family, which is named after the forkhead winged-helix DNA-binding domain, 23 has been reported to act as important regulators of numerous biological processes, including cell cycle regulation, proliferation, differentiation, senescence, survival, metabolism and apoptosis. 24,25 A series of FOX genes, such as FOXC2, 26,27 FOXJ1, 28 FOXL1, 29 FOXM1, [30][31][32][33][34][35] and FOXPs, [36][37][38] have been reported to play vital roles in the carcinogenesis, metastasis and prognosis of ccRCC. A previous study reported that FOXK2 expression was elevated in human colorectal cancer and is associated with intestinal tumorigenesis; 20 two other studies reported that FOXK2 was downregulated in breast cancer and suppressed the carcinogenesis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, overexpression of FOXM1 was correlated with the poor prognosis of patients with malignant tumors and has been reported in many types of cancers including GC (2832). Zhang et al reported that downregulation of FOXM1 suppressed PLK1-regulated cell cycle progression in renal cancer cells (33). Additionally, Inoguchi et al found that microRNA-24-1 inhibited bladder cancer cell proliferation by targeting FOXM1 (34).…”
Section: Discussionmentioning
confidence: 99%